A CHILD STRUGGLE TO SURVIVE IN A CHILD CALLED IT NOVEL BY DAVE PELZER (1995): A HUMANISTIC PSYCHOLOGICAL APPROACH - KHOLIFAH, YUNIATI (2011)
The major problem of this study is how a child struggle to survive is reflected in A Child Called It novel by Dave Pelzer. The aim of this study is to analyze the novel based on the structural elements and to analyze the novel based on the humanistic psychological approach. This study belongs to qualitative method. In this method, there are two types of data source, namely primary and secondary data source. The primary data source is A Child Called It novel itself, while secondary data are taken from some information needed. The benefit of this study is to give additional information which can be used by other literature researchers who are interested in analyzing this novel. Based on the analysis the writer draws some conclusion as follows. First, the story of this novel is based on true story. There is a struggle to survive. So, it has relationship between the struggle and Humanistic Psychological. Second, after analyzing the structural elements of the novel, it can be concluded that all the structural elements, namely, Character and characterization, setting, plot, point of view, theme, and figurative language has a unity. Finally, the humanistic psychological analysis shows that people will do everything to achieve their goal. Dave pelzer, as the main character describes and shows his struggle to fulfill the needs which are evaluated in Humanistic Psychological approach. Dave only can complete the first basic need, physiological needs, and it is not easy.